Exploring how adaptive leadership is enacted and experienced in the South African aviation industry, and how it influences employee adaptive performance in a complex and evolving operational context - Joseph Renjini (University of Pretoria, 2026)
Mini Dissertation (MPhil (Change Leadership))--University of Pretoria, 2025.